Joint spectrum sensing, power and bandwidth allocation for multiband cognitive radio systems - Mohammad Karimi; Shadi Ahmadi (IET Communications, 2021)
Abstract Multiband cognitive radio (CR) signaling allows CR networks to efficiently take advantage of the unused frequency bands. Joint spectrum sensing and power allocation in CR systems has been shown to provide higher opportunities for CR transmission. In this work, joint spectrum sensing and resource allocation (power and bandwidth) are performed in a multiband CR system. This is achieved by defining an optimization problem which is formulated with the aim of minimizing CR network outage probability. It is shown that minimizing the outage probability of CR network is equivalent to maximizing the CR network achievable data rate. Hence, the related optimization problem converts to maximizing the average opportunistic CR data rate under constraints on interference, power budget and total available bandwidth leading to a non‐convex optimization problem. As the original formulated optimization problem is inherently non‐convex, it is converted into a convex problem where the optimal solution is obtained using the Lagrange multipliers method and linear programming. For performance comparison, the classical method based on equal bandwidth allocation for each subchannel is considered. Several numerical results are provided to contrast the performance of the proposed method compared to the classical method, in terms of the average achievable CR data rate.